SELECTION OF INVESTMENT PROJECTS IMPLEMENTATION OPTIONS - A. V. Kozlovsky; N. A. Moiseenko; O. E. Astafieva (Вестник университета)
The main unresolved issues of choosing the most effective investment projects aimed at introducing innovative technologies have been considered. The traditional indicators of investment efficiency have been analysed. The expediency of using the indicator of the total reduced costs necessary for the implementation of the project has been substantiated. Attention has been paid to the possibilities of public-private partnership in innovation projects. The issues of shares distribution between participants in innovation and investment projects and the use of such objects have been reviewed. The current situation in the investment and construction sector of the economy has been assessed and ways to solve the main problems of investment activity in the construction industry have been outlined. The expediency of creating a mechanism for economic justification of the investment project implementation process, including the creation of reserve funds, has been substantiated. Recommendations for using the indicator of the of the investor’s total stated costs have been given.